O Centro de Educação da Polícia Militar: história e memória do ensino militar na Paraíba (1990-2016) - Andrade, Vânia Cecília de Lima (2019)
The present project seeks to give visibility to Military Teaching at Paraíba by the history rebuilding of the Centro de Educação da Polícia Militar – CEPM at the comprehended period between 1990 and 2010. We used the oral history methodology to do the reconstitution of the individual and collective memories of the interviewed people, letting the dialog between these oral sources, considering the locus of the respondent speech. Meihy and Holanda (2017) are used to explain how the oral history was precious to the rebuilding of these historical facts, because let us to analyze the subject speeches, seeing not only the different places where they spoken, but opportuning us to confront them with the found written and iconographic sources. Le Goff (2003), Pollak (1992) and Halwbachs (2006) ideas, for seek to elucidate how the memory of an individual can be, as social building, imbricate of components that denote a “belonging” to a certain collectivity, forging an identify apparatus, deserved highlight at the discussion about the speech respondent also. We realized that giving visibility to CEPM history brought up the PMPB organizational culture, that directs CEPM educative actions, showing, beyond pedagogical practices developed at the Center, the fortification of the institutional link of the militaries at graduation, by a set of signs and symbolic representations of that collectivity.